An Analysis of the Appropriate Number of Workers in Elderly Care Hospital by Pathfinder in Korea - et. al., Hong-Sang Lee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study estimated the appropriate number of employees that are able to evacuate all occupants during the daytime and nighttime through an evacuation simulation. During the daytime, 200 patients and 44 workers evacuated after 416 se This result showed that the number of workers was greater than the standard number of daytime worker placements because this record was faster than the Korean Fire Department’s average arrival time of 430 seconds. Therefore, the appropriate number of workers during the daytime for all occupants to escape within the Korean Fire Department’s average arrival time of 430 seconds is 30 persons, 25 persons for the standard evacuation time of 480 seconds, and 20 persons for the average time of flashover of 540 seconds. During the nighttime, a total of 205 people, including 200 patients and 5 workers, needed 1,475 seconds to evacuate. As this time exceeds the average time of flashover, it was shown that the number of workers was fewer than the standard number of nighttime worker placements. Therefore, the appropriate number of workers at nighttime is 35 persons for 430 seconds, 30 persons for 480 seconds, and 25 persons for 540 second